Meteorological measurements at Concordia Station in 2009 - Vitale, Vito (Institute of Atmospheric Sciences and Climate of the Italian National Research Council, Bologna, 2025)
The meteorological measurements at Concordia station are part of the BSRN radiation measurements (see Related to references) but were only published in 2025.